Polycefin, a New Prototype of a Multifunctional Nanoconjugate Based on Poly(β-l-malic acid) for Drug Delivery - Lee, Bong-Seop (2006)
A new prototype of nanoconjugate, Polycefin, was synthesized for targeted delivery of antisense oligonucleotides and monoclonal antibodies to brain tumors. The macromolecular carrier contains: 1. biodegradable, nonimmunogenic, nontoxic β-poly(l-malic acid) of microbial origin; 2. Morpholino antisense oligonucleotides targeting laminin α4 and β1 chains of laminin-8, which is specifically overexpressed in glial brain tumors; 3. monoclonal anti-transferrin receptor antibody for specific tissue targeting; 4. oligonucleotide releasing disulfide units; 5. l-valine containing, pH-sensitive membrane disrupting unit(s), 6. protective poly(ethylene glycol); 7. a fluorescent dye (optional). Highly purified modules were conjugated directly with N-hydroxysuccinimidyl ester-activated β-poly-(l-malic acid) at pendant carboxyl groups or at thiol containing spacers via thioether and disulfide bonds. Products were chemically validated by physical, chemical, and functional tests. In vitro experiments using two human glioma cell lines U87MG and T98G demonstrated that Polycefin was delivered into the tumor cells by a receptor-mediated endocytosis mechanism and was able to inhibit the synthesis of laminin-8 α4 and β1 chains at the same time. Inhibition of laminin-8 expression was in agreement with the designed endosomal membrane disruption and drug releasing activity. In vivo imaging showed the accumulation of intravenously injected Polycefin in brain tumor tissue via the antibody-targeted transferrin receptor-mediated endosomal pathway in addition to a less efficient mechanism known for high molecular mass biopolymers as enhanced permeability and retention effect. Polycefin was nontoxic to normal and tumor astrocytes in a wide range of concentrations, accumulated in brain tumor, and could be used for specific targeting of several biomarkers simultaneously.